Continuation of Aspirin Therapy before Cataract Surgery with Different Incisions: Safe or Not? - Qingjian Li; Yiwen Qian; Yu Zhang; Gaoyuan Sun; Xian Zhou; Zhiliang Wang (Journal of Ophthalmology)
Purpose. To assess whether to continue aspirin therapy while having uncomplicated phacoemulsification cataract surgery with different incisions. Methods. Consecutive patients having cataract surgery under topical anesthesia with different incisions between May 2016 and August 2017 were followed. 236 eyes of 166 patients on routine aspirin therapy were randomized into 2 groups: continuation group, 112 eyes; discontinuation group, 124 eyes. 121 eyes of 94 patients on no routine anticoagulant therapy were used as the control group. Patients were examined 1 day preoperatively and 1 day and 7 days postoperatively. Intraoperative and postoperative complications were recorded. Results. Statistically, there was no significant difference about postoperative BCVA among three groups. A higher incidence of subconjunctival hemorrhage was shown in the continuation group than in the discontinuation group and the control group (17.0% versus 8.1%, p=0.038; 17.0% versus 7.4%, p=0.025, resp.). Although corneal edema was greater in clear corneal incision cases than that of scleral tunnel incision cases (22.5% versus 12.0%, p=0.009), subconjunctival hemorrhage was greater in scleral tunnel incision cases (14.9% versus 6.6%, p=0.011). Subgroup analyses revealed that patients of scleral tunnel incision who continued taking aspirin had a higher incidence of subconjunctival hemorrhage compared with those who discontinued (25.5% versus 10.9%, p=0.038), but no same conclusion in clear corneal incision cases (8.8% versus 5.0%, p=0.483). Conclusions. The outcomes indicated that phacoemulsification cataract surgery under topical anesthesia could be safely performed without ceasing systemic aspirin therapy. Clear corneal incision could be a better choice in patients treated with aspirin.